Experimental values of solubility of organic compounds in water for a wide range of temperature values - a new experimental technique - J. M. P. Q. Delgado (2010)
This paper describes a simple experimental technique, easy to set-up in a laboratory, for the measurement of solute solubility in liquids (or gases). Experimental values of solubility were determined for the dissolution of benzoic acid in water and salicylic acid in water, at temperatures between 5ºC and 70ºC. The solubility experimental values obtained are in good agreement with the theoretical values of solubility and the empirical correlations presented in literature. The results show that it is possible to obtain good results for solubility values, using a simple and inexpensive experimental technique.